Early Intervention for Low-Temperature Burns: Comparison between Early and Late Hospital Visit Patients - Matthew Seung Suk Choi; Ho Joon Lee; Jang Hyun Lee (Archives of Plastic Surgery, 2015)
Background Various focal heating devices are popular in Korea under the cultural influence of the traditional ondol under-floor method of home heating. These devices can cause severe burn-like injuries resulting from device malfunction or extended with low heat contact. In addition to injuries under these high heat contact, burns can be occurred by low heat exposure with prolonged periods despite the devices are properly functioning. In order to develop strategies to reduce the duration of periods of illness due to low-temperature burns, we analyzed and compared treatment methods and therapeutic periods for this type of injury. Methods This retrospective study included 43 patients burned under low heat conditions. Patients were divided into an operative group and a conservative group. The patients in the operative group underwent at least one surgical excision, and were further subdivided into early and late visit groups. The conservative group was treated only with dressings. We compared the treatment periods between the operative group and the conservative group, and also compared the preparation periods and treatment periods between the two operative groups. Results The average treatment period was significantly shorter in the operative group (P=0.02). In the early visit operative group, both wound preparation and treatment were briefer than in the late visit group. Conclusions We recommend that early proper burn care and early surgical intervention, including appropriate excision, are feasible ways to reduce the treatment period of low-temperature burn patients.